Los Zetas Inc. Criminal Corporations, Energy, and Civil War in Mexico - Correa-Cabrera, Guadalupe (University of Texas Press, 2021)
The rapid growth of organized crime in Mexico and the government's response to it have driven an unprecedented rise in violence and impelled major structural economic changes, including the recent passage of energy reform. Los Zetas Inc. asserts that these phenomena are a direct and intended result of the emergence of the brutal Zetas criminal organization in the Mexican border state of Tamaulipas. Going beyond previous studies of the group as a drug trafficking organization, Guadalupe Correa-Cabrera builds a convincing case that the Zetas and similar organizations effectively constitute transnational corporations with business practices that include the trafficking of crude oil, natural gas, and gasoline; migrant and weapons smuggling; kidnapping for ransom; and video and music piracy. Combining vivid interview commentary with in-depth analysis of organized crime as a transnational and corporate phenomenon, Los Zetas Inc. proposes a new theoretical framework for understanding the emerging face, new structure, and economic implications of organized crime in Mexico. Correa-Cabrera delineates the Zetas establishment, structure, and forms of operation, along with the reactions to this new model of criminality by the state and other lawbreaking, foreign, and corporate actors. Since the Zetas share some characteristics with legal transnational businesses that operate in the energy and private security industries, she also compares this criminal corporation with ExxonMobil, Halliburton, and Blackwater (renamed "Academi" and now a Constellis company). Asserting that the elevated level of violence between the Zetas and the Mexican state resembles a civil war, Correa-Cabrera identifies the beneficiaries of this war, including arms-producing companies, the international banking system, the US border economy, the US border security/military-industrial complex, and corporate capital, especially international oil and gas companies